Development of Local Cultural Tourism Communication Model to Promote Tourism in Nakhon Si Thammarat Province Using Conjoint Analysis Technique - Suwanacheep, Pelapon; Nillakan, Lunjakon; Lertgrai, Panya (Ratchaphruek Journal, 2025)
This study aimed to analyze the characteristics of local cultural tourism communication through virtual tours that satisfy tourists. The researcher collected all relevant characteristics of virtual tours through a literature review process and selected the five most important virtual tour characteristics using the Analytic Hierarchy Process (AHP). These characteristics were then used to design a questionnaire using conjoint analysis techniques. The sample group consisted of 200 tourists aged 18-70 years who visited Mueang District, Nakhon Si Thammarat Province. Data were collected through questionnaires and analyzed using conjoint analysis techniques, while satisfaction values were calculated using linear regression analysis. The findings revealed that the most important characteristic for general tourists was the local cultural tourism communication through virtual tours that incorporated both real and graphic panoramic images, presented through either tourism routes or game-based learning, with a 5-minute viewing duration, featuring 3D models, and accompanying videos.